168 β-Blocker therapy improves clinical outcomes in patients with moderate to severe mitral regurgitation. (9th June 2011) - Nadir, A; Elder, D H; MacArtney, M G; Pringle, S D; Choy, A M; Struthers, A D; Lang, C C
Abstract : Background: Volume overload seen in mitral regurgitation (MR) leads to neuro-endocrine activation including heightened sympathetic activity. Experimental data have reported protective effects of beta-blockers (BBs) on myocardial function in MR suggesting that BB therapy may be beneficial in MR. However, the effect of BB therapy on clinical outcomes in MR has not been defined. Hence, in this large observational study we investigated the impact of BB therapy on clinical outcome in patients with moderate to severe MR. Methods: The Health Informatics dispensed prescribing, morbidity and mortality database for the population of Tayside, Scotland was linked through a unique patient identifier to the Tayside echocardiography database (>110 000 scans). Patients with a diagnosis of moderate or severe MR from 1993 to 2008 were identified. Cox regression model (adjusted for age, gender, left ventricular dimensions and function, left atrial diameter, cardiovascular (CV) history and concurrent CV medications) was used to assess the impact of BB therapy on all-cause mortality and cardiovascular events (CV death or hospitalisations). Results: A total of 4437 patients with moderate to severe MR (mean age 74 Â±11 years, 46% males) were identified. MR was categorised as functional in 2523 (57%) and organic in 1894 (43%) while 1324 (30%) were on BBs. Over a mean follow-up of 3.9 years there were 2287 (51%) all-cause deaths and 2333 (52%) CV events. Those treated with BBs had a significantly lower all-cause mortality with an adjusted HR of 0.65 (95% CI 0.56 to 0.75, p<0.0001) and fewer CV events with an adjusted HR of 0.79 (95% CI 0.69 to 0.90, p<0.0001). Conclusions: This large observational study suggests that BB therapy is associated with an improved survival and a lower risk of CV events in patients with moderate to severe MR. These observations needs to be confirmed in prospective studies and support the rationale for undertaking a future randomised clinical trial.